A study of droplet impact on static films using the BB-LIF technique - Hann, David B.; Cherdantsev, Andrey V.; Mitchell, A.; McCarthy, I.N.; Hewakandamby, Buddhika N.; Simmons, Kathy
This paper presents results of single droplet impacts on films of different height taken using the Brightness Based Laser Induced Fluorescence technique (BB-LIF). The dynamics of drop impingement such as the shape of the cavity, residual film thickness are investigated and analysed with a time-resolution of 0.1 ms and spatial resolution of 70 um. Additionally a variation of the BB-LIF technique is used to investigate the change in profile of the droplet liquid during the inertial self-similar regime. The results of the analysis show that present models predicting initial development of the cavity show good agreement. Suggested amendments for some of the constants for cavity width and residual film thickness are proposed based on the film thickness, that fit better with published data. The development of the profile of the droplet liquid demonstrates that for thin liquid films, the droplet liquid behavior with strong similarity to droplet impact on dry solid surfaces. It is noted that for some of the measured parameters, the use of the film height as the lengthscale gives a better fit.